Mechanochemical Synthesis of WC Powders by Mechanical Alloying - Öveçoğlu, M. Lutfy; Özkal, Burak (Trans Tech Publications, Ltd., 2004)
A WC powder alloy was synthesized by mechanical alloying of elemental tungsten and graphite powders. Mechanical alloying runs were carried out in a heavy-duty attritor and subsequently in a Spex Mixer-Mill at room temperature. X-ray investigations conducted on the attritor-milled powders revealed only the presence of the W phase and the indication of carbon amorphization with milling time. When the attritor-milled powders were annealed at 1100 °C, metastable and stable WCx phases emerged in the microstructure. Progressive Spex milling of the powders attritor-milled for 30 h was carried out to follow the transformation of into the stable WC phase which was achieved between 20 and 30 h during Spex milling. Analytical transmission electron microscopy experiments on the Spex milled powders verified the presence of the WC powder particles.